If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6(-2x + 18) = 157 Reorder the terms: 5x + 6(18 + -2x) = 157 5x + (18 * 6 + -2x * 6) = 157 5x + (108 + -12x) = 157 Reorder the terms: 108 + 5x + -12x = 157 Combine like terms: 5x + -12x = -7x 108 + -7x = 157 Solving 108 + -7x = 157 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-108' to each side of the equation. 108 + -108 + -7x = 157 + -108 Combine like terms: 108 + -108 = 0 0 + -7x = 157 + -108 -7x = 157 + -108 Combine like terms: 157 + -108 = 49 -7x = 49 Divide each side by '-7'. x = -7 Simplifying x = -7
| 2(4x-3)-8=4+sx | | 7x-7-5x=19 | | h=-16t(t-5) | | 2/5-45888/2222 | | C+25=415 | | 7m=(m-4) | | -3(4-a)=-6 | | S=1/5(65-5e) | | 5x-3+3x+45=90 | | 4x-18+90=180 | | y=(x+3)(x^2+25)(x^2-2x+10) | | -3(4-a)=-15 | | -2n-12=-6(2+6n) | | 96=15+9s | | 5x+6(-2+18)=157 | | 5(n+3)=3(2*n-1) | | 8y-3y=35 | | 5x+6(-2+18)=108 | | 4y=3x+C | | 63/w=9 | | 12x=5(8+2x) | | h=-2(t-1)-16t(t-1) | | XP+to=z | | 8m+10=50 | | 4(x-5)+6=2(2x-7) | | x*5+65=4*x | | 24+5h=89 | | 10x-3/12 | | X^2-9x-19/x-2 | | 2x-54=104 | | 2(x+3)+x+7=2(3x+9)+5(4-x)+3 | | 4(3x+8)=32 |